Pengembangan Media Pembelajaran Berbasis Audio Visual Untuk Siswa Kelas X Ipa - Al Fitani, M. Saliman; Gazali, Zulkarnain (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
The objectives of this study were: (1) to produce of learning media based on audio visual for teaching materials of virus, and (2) to determine the advisability of the learning media. The learning media developed using the 4D Thiagarajan model. But, this study only used three steps, which were define, design, develop steps. The result of validation scores showed that the learning media audio visual of virus materials was very advisible to be used.